Impact of Citizen Charter on Service Delivery: A Case Study of District Administration Office, Dolakha - Bhandari, Rita (Journal of Kathmandu BernHardt College, 2025)
The Citizen Charter, introduced in Nepal through the Good Governance (Management and Operation) Act, 2007, aims to make public service delivery more transparent, accountable, and citizen-focused. Rooted in the ideas of New Public Management and Principal–agent theory, it emphasizes efficiency, responsiveness, and better engagement with the public.This study evaluates how the Citizen Charter is being implemented at the District Administration Office, Dolakha, focusing on its influence on service delivery, public awareness, and grievance handling. The results show that the Charter has helped improve access to information and shaped citizens’ perceptions positively. However, service delivery performance remains weak, with only 26% of services provided within the promised timeframe. Interestingly, 74% of respondents still expressed satisfaction, indicating that people tend to accept minor delays if the services are dependable. Awareness levels, however, were low—only 43% of citizens knew about the Charter, and just 27% fully understood its provisions. While many citizens felt adequately informed, grievance and complaint systems were not used effectively. Only 37% had filed complaints, and of those, just 32% received responses.